The Influence of Service Quality and Price Perception on Customer Satisfaction in the Shopee Marketplace Mediated by Customer Reviews (Empirical Study: Shopee Consumers in Jakarta) - Velisia Ananda Harto; Liem Bambang Sugiyanto (Pelopor Publikasi Akademika, 2025)
The purpose of this study is to examine the effect of service quality and price perception on customer satisfaction, as well as to explore the role of customer reviews as a mediating variable among Shopee consumers in Jakarta. This research was conducted using an online survey with 200 respondents who met the criteria of having made a transaction on Shopee within the last 6 months and have provided reviews for the products purchased. The study employs a quantitative approach using a structural equation modeling (SEM) model, processed with AMOS 24 software. The scope of this research is limited to Shopee consumers in Jakarta, and the survey was conducted over a period of one month, from December 2024 to January 2025. The respondents in this study were only those residing in Jakarta. This research aims to understand the impact of service quality and price perception on customer satisfaction, with customer reviews serving as a mediating factor. The findings of this study are expected to provide valuable insights for marketers and producers in designing competitive service and pricing strategies to enhance customer satisfaction.